Photoinduced Electron Transfer between Psoralens and DNA: Influence of DNA Sequence and Substitution. Issue 9 (26th November 2015) - Fröbel, Sascha; Levi, Lucilla; Ulamec, Sabine M.; Gilch, Peter
Abstract: Psoralens are heterocyclic compounds which are, among other uses, used to treat skin deseases in the framework of PUVA therapy. In the dark, they intercalate into DNA and can form photoadducts with thymines upon UV‐A excitation, which harms the affected cells. We have recently discovered that after excitation of intercalated psoralens, an efficient photoinduced electron transfer (PET) from DNA occurs. Here, the PET is studied in detail by means of femtosecond transient absorption spectroscopy. Using DNA samples that contain either only GC or AT base pairs, we show that only guanine donates the electrons. Additionally, the substituent effects on PET are studied relying on three different psoralen derivatives. The substitution alters spectroscopic and electrochemical properties of the psoralens, which are determined by cyclic voltammetry and steady state spectroscopy. These experiments allow us to estimate the PET energetics, which are in line with the measured kinetics. Implications for the applications of psoralens are discussed. Abstract : Electrons in the way : A recently discovered photoinduced electron transfer appears to hamper the therapeutic effects of psoralens within DNA. This transfer is studied in detail through femtosecond spectroscopy. The experiments may reveal new approaches for the optimization of psoralens with respect to their reactivity.